Manajemen Perianestesi Subarachnoid Block Pada Pasien ORIF Fraktur Femur Dextra: Studi Kasus - Abdurrahman, Muhammad Farhan; Agniansyah, Kakha; Delfiando, Dicky; Larasati, Putri; Susanto, Amin; Sebayang, Septian Mixrova (Pustaka Galeri Mandiri, 2026)
Femoral fracture is a major orthopedic injury requiring operative management to prevent complications and restore limb function. Anesthetic technique plays a crucial role in the success of surgical intervention. This case report employed a descriptive observational method with a case study approach on a 36-year-old male patient with a complete fracture of the middle third of the right femur who underwent Open Reduction and Internal Fixation (ORIF). Data were collected from medical records, physical examination, laboratory tests, radiological findings, as well as intraoperative and post-anesthesia monitoring. Anesthetic management was performed using spinal anesthesia with 15 mg of intrathecal bupivacaine, supported by multimodal analgesia and fluid therapy to maintain hemodynamic stability. During surgery, the patient remained stable, although shivering occurred and was successfully managed with intravenous pethidine and external warming. Post-anesthesia, the patient demonstrated gradual motor recovery, stable vital signs, and no serious complications. In conclusion, spinal anesthesia proved effective in providing adequate analgesia, maintaining hemodynamic stability, and reducing intraoperative complications in patients undergoing ORIF for femoral fracture. This case highlights the importance of selecting an appropriate anesthetic technique, close monitoring, and prompt intervention to ensure patient safety and favorable clinical outcomes